Factors Influencing The Implementation of Comprehensive Emergency Obstetric and Neonatal Services (PONEK) at Restu Ibu Hospital Balikpapan - Hendra Susanto; Asriwati Amirah; Ramadhani Syafitri Nasution (PROMOTOR, 2026)
The 24-hour PONEK hospital is part of the maternal and neonatal emergency care referral system, which plays a significant role in reducing maternal and neonatal mortality rates. The key to PONEK's success is the availability of competent healthcare workers, reliable infrastructure, facilities, and management. The purpose of this study was to analyze the factors influencing the implementation of Comprehensive Emergency Obstetrics and Neonatal (PONEK) services at Restu Ibu Hospital in Balikpapan. Methodology: The research design used in this study was an analytical survey with a cross-sectional design. The population in this study was all medical personnel involved in the PONEK Program at Restu Ibu Hospital, Balikpapan, totaling 57 people. The number of samples to be studied was 57 people. Data analysis was performed using univariate, bivariate, and multivariate analysis. Statistical tests used were the chi-square test and logistic regression. Results: The results of the chi-square test showed that the independent variables, namely communication, resources, disposition, and bureaucratic structure, had a p-value of 0.001 < 0.05, meaning that communication, resources, disposition, and bureaucratic structure influenced the implementation of PONEK at Restu Ibu Hospital in Balikpapan. The most dominant factor that influenced this was communication with an odds ratio (OR) of 5.969. Conclusion: The conclusion is that communication, resources, disposition and bureaucratic structure influence the implementation of PONEK at Restu Ibu Hospital Balikpapan. It is recommended that good support and commitment from the hospital director and owner's representatives by building good communication with the PONEK team by inviting and involving all PONEK activities, Building good communication among PONEK Teams by participating in effective communication training, Building a skilled team by budgeting training plans related to PONEK so that it is hoped that all PONEK Teams have participated in training according to standards, Equipping adequate room facilities and infrastructure according to PONEK Hospital criteria, conducting MoUs with professional organizations, Building and fostering referral networks.